A paisagem sonora de Os sinos da agonia, de Autran Dourado - Gonçalves, Alcides Fernando Campos (2023)
In this paper, we seek to analyze the role played by musical and sonic aspects in the novel Os sinos da agonia, by Autran Dourado. To do so, we employ the concept of soundscape, coined by Raymond Murray Schafer (2011) and introduced by Gérson Werlang (2011) in the scope of literary theory. When referring to our acoustic environment, that is, the set of sounds that make up our daily life, Schafer (2011) states that the soundscape can provide an important testimony about the space or time in which it is inserted. Furthermore, a sound event can carry a symbology and act in a specific way on the human unconscious. Thus, we investigated the novel's soundscape from two angles: firstly, in view of the historical setting of the narrative, whose action takes place in Vila Rica in the mid-18th century. From this, we discovered aspects related to the cultural and artistic formation of the province of Minas Gerais. Secondly, we analyzed the soundscape in relation to the thematic composition of the novel, more precisely the intertextual relationship it maintains with the tragic genre. We thus sought to establish some correspondences between the role of the soundscape in the construction of the narrative and the participation of lyrical elements in the creation of dramatic tension in tragedy.